Northern tamarisk beetle (Diorhabda carinulata) and tamarisk (Tamarix spp.) interactions in the Colorado River basin. Issue 2 (25th August 2017) - Nagler, Pamela L.; Nguyen, Uyen; Bateman, Heather L.; Jarchow, Christopher J.; Glenn, Edward P.; Waugh, William J.; van Riper, Charles
Abstract : Northern tamarisk beetles ( Diorhabda carinulata ) were released in the Upper Colorado River Basin in the United States in 2004–2007 to defoliate introduced tamarisk shrubs ( Tamarix spp.) in the region's riparian zones. The primary purpose was to control the invasive shrub and reduce evapotranspiration (ET) by tamarisk in an attempt to increase stream flows. We evaluated beetle–tamarisk interactions with MODIS and Landsat imagery on 13 river systems, with vegetation indices used as indicators of the extent of defoliation and ET. Beetles are widespread and exhibit a pattern of colonize–defoliate–emigrate, so that riparian zones contain a mosaic of completely defoliated, partially defoliated, and refoliated tamarisk stands. Based on satellite data and ET algorithms, mean ET before beetle release (2000–2006) was 416 mm/year compared to postrelease (2007–2015) ET of 355 mm/year ( p < 0.05) for a net reduction of 61 mm/year. This is lower than initial literature projections that ET would be reduced by 300–460 mm/year. Reasons for the lower‐than‐expected ET reductions are because baseline ET rates are lower than initially projected, and percentage ET reduction is low because tamarisk stands tend to regrow new leaves after defoliation and other plants help maintain canopy cover. Overall reductions in tamarisk green foliage during the study are 21%. However, ET in the Upper Basin has shown a steady decline since 2007 and equilibrium has not yet been reached. Defoliation is now proceeding from the Upper Basin into the Lower Basin at a rate of 40 km/year, much faster than initially projected.